TRACE ELEMENT FRACTIONATION IN COEXISTING HIGH- AND LOW-CA ALKALI ULTRAMAFIC SERIES OF THE ODIKHINCHA MASSIF (POLAR SIBERIA) - Rass I.T. (My University, 2004)
Trace element distribution in melilite-bearing and melilite-free rocks and their minerals is studied for Odikhincha, a typical alkali ultramafic ring-type massif in the northwestern Siberian Platform. The melilite-bearing rocks (high-Ca series) have higher Sr contents (by about ten times), REE contents, and LREE/HREE ratios. The melilite-free rocks (low-Ca series) have higher P contents. Sr, REE, Nb, and Zr fractionation in both series is consistent with the Rayleigh model of fractional crystallization at various partition coefficients of these elements, which are related to differences in composition of primary magmas for these series and conditions of their formation and differentiation. Notable differences, which were revealed in trends of pyroxene, magnetite, perovskite, and apatite zoning in differentiates of both series, reflect specific features of the high-Ca and low-Ca magma differentiation.